1999
DOI: 10.1006/viro.1999.9817
|View full text |Cite
|
Sign up to set email alerts
|

Equine Arteritis Virus Derived from an Infectious cDNA Clone Is Attenuated and Genetically Stable in Infected Stallions

Abstract: Virus derived from an infectious cDNA clone of equine arteritis virus (EAV030H) was intranasally inoculated into two stallions, neither of which subsequently developed clinical manifestations of equine viral arteritis (EVA). Virus was isolated from nasal swabs and mononuclear cells collected from both stallions Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 26 publications
1
55
0
Order By: Relevance
“…The presence of EAV-specifi c antibodies in the horse blood serum is one of the evidence of the presence of the disease, which has been confi rmed also in our study by fi ndings of high antibody titre values in breeding stallions and mares [6,12,14]. High antibody titre and seroprevalence in stallions (45%) and mares (65%), without clinical signs strongly suggest the long-lasting presence of the disease at a horse stable [8].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The presence of EAV-specifi c antibodies in the horse blood serum is one of the evidence of the presence of the disease, which has been confi rmed also in our study by fi ndings of high antibody titre values in breeding stallions and mares [6,12,14]. High antibody titre and seroprevalence in stallions (45%) and mares (65%), without clinical signs strongly suggest the long-lasting presence of the disease at a horse stable [8].…”
Section: Discussionsupporting
confidence: 84%
“…The fi rst anti-EAV antibodies can be detected 7-14 days after infection. The highest levels of antibodies are detectable in the period 2-4 months post infection, and they can persist for 3 or more years [6,12]. Antibody titre values higher than 2 log 2 are considered positive in VNT [13].…”
Section: Introductionmentioning
confidence: 99%
“…The virus infects the smaller blood vessels, especially the arterioles, causing a panvasculitis (16,35,42). A number of studies have demonstrated that different strains of EAV vary significantly in their pathogenicity, with very different clinical outcomes upon experimental inoculation of horses (2,5,6,21,43). The horseadapted virulent Bucyrus (VB) strain of EAV is highly velogenic and causes severe clinical disease with a case fatality rate of 50 to 60% under experimental conditions (35,51).…”
mentioning
confidence: 99%
“…Horses inoculated with virulent strains of EAV (e.g., the VB, recombinant VB [rVBS], and KY84 strains) develop severe lymphopenia with a high-titer viremia (6 ϫ 10 3 to 1 ϫ 10 5 PFU/ml) (2,5,35,44). In contrast, horses inoculated with the attenuated modified live virus (MLV) vaccine strain or other avirulent strains of EAV (e.g., 030H and CA95G) (6,49) develop a mild, transient lymphopenia with only a very-low-titer viremia (Յ1 ϫ 10 1 PFU/ml) (20,24,(37)(38)(39)(40). The MLV vaccine (ARVAC; Fort Dodge Animal Health, Fort Dodge, IA) that is in current use in the United States and Canada (20,(37)(38)(39)(40) (24).…”
mentioning
confidence: 99%
“…Reverse genetic systems are a powerful tool for the molecular dissection of arteriviruses and infectious cDNA clones have been developed for equine arteritis virus and traditional PRRSV strains (Balasuriya et al, 1999(Balasuriya et al, , 2007Meulenberg et al, 1998;van Dinten et al, 1997;Wang et al, 2008). In this study, we set out to construct infectious cDNA clones of HP PRRSV to further clarify the role of this virus as the major aetiological agent of PHFS.…”
mentioning
confidence: 99%